A microstructural, mechanical and electrochemical/stress corrosion cracking investigation of a Cr-modified Ti–6Al–4V alloy - Stephen Yeboah Boakye; Kyoungdoc Kim; Jaekook Kim; Jong-Sook Lee; Jungmuk Choi; Sam Yaw Anaman; Hoon-Hwe Cho (Journal of Materials Research and Technology, 2023)
The microstructural effects of a Cr-modified Ti–6Al–4V (Ti64) alloy on the mechanical, electrochemical and stress corrosion cracking properties were studied. With the aid of thermodynamic calculations and microstructural characterizations, Ti64–3Cr forged alloy was successfully fabricated with no defects by micro-alloying Ti64 with 3 wt% Cr. The microstructure features of the Ti64–3Cr alloy reveal fine alpha laths with a lamellar structure and strong texturing particularly in the basal and prismatic poles. The mechanical results at room temperature show enhanced yield strength and hardness attributed to the refined alpha laths and solid solution strengthening effect caused by Cr addition. Afterward, the electrochemical properties were investigated under different NaCl electrolyte concentrations. The alloy showed good corrosion resistance in the various NaCl concentrations as a result of the formation of Cr2O3 oxide due to the alloying effect of Ti64–3Cr alloy. X-ray photoelectron spectroscopy was used to confirm the presence of the oxides film on the surface of the alloy after the electrochemical studies. Furthermore, the stress corrosion cracking (SCC) properties of the alloy were investigated using a strain rate of 1 × 10−6 s−1 in 3.5 wt% NaCl aqueous solution under different temperatures. The results showed that as the temperature increased during slow strain rate testing, the SCC susceptibility of the alloy decreased. The outstanding SCC strength and enhanced corrosion properties of the novel alloy could serve as a potential use in marine applications.